The new accountability : environmental responsibility across borders - Mason, Michael, 1966- (London ; Sterling, VA : EARTHSCAN, 2005)
"Drawing on case studies, this book provides a fresh understanding of democratic accountability for transboundary and global harm and argues that environmental responsibility should be established in open public discussions about harm and risk"--Provided by publisher.
1. Transnational accountability for environmental harm : a framework -- 2. Advocates for environmental accountability : activist groups, networks and movements -- 3. Citizenship beyond national borders? : affected publics and international environmental regimes -- 4. The world trade regime and environmental accountability -- 5. Transnational liability for environmental damage -- 6. The environmental accountability of transnational corporations.
Includes bibliographical references (p. [179]-196) and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Environmental protection -- International cooperation; Environmental policy -- International cooperation; Environmental responsibility; Electronic books